PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PEMBIAKAN TANAMAN SECARA VEGETATIF DENGAN MENGGUNAKAN METODE MIND MAP PADA SISWA KELAS X ATPH SMKN 3 TAKALAR - Ratnasari, Ratnasari; Fatah, Anwar; Nur, Hasanah (Universitas Negeri Makassar, 2015)
This is class action research which aimed to improve the student’s achievement in plant propagation vegetative subject especially in transplanting and cultivation material atthe X class in SMK Negeri 3 ATPH Takalar. The subjects of this research consisted of 35 student’s. The data that has been collected; is analyzed using quantitative and qualitative data. Based on the result of the research, it can be concluded that the aplication of Mind Mapping method can improve the student’s achievement. The result of the pre-cycle, cycle I and cycle IIthat has a significant improvement. Before applying Mind Mapping method, the student’s average score is about 54.15 with standard completeness 17.14%, the value of student’s learning achievement in cycle I average 71,82 with standard completeness 71,42%, but it is not fulfilled on the standard classical completeness 85%, so that it is continued to the cycle II. After reflecting on the cycle I, a significant improvement of the student’s achievement in the cycle II increase average score 79.04 with standard completeness 91.42%. In the other words, the student’s achievement is fulfilled on minimal completenessstandard and classical completeness standard > 85%